Optimization of Scheduling using Heuristic Approach with Campbell Dudek Smith Algorithm (CDS) at PT OSIN - Raihan Afif Makarim; Apid Hapid Maksum; Muhamad Taufiq Rachmat (Jurnal Rekayasa Sistem & Industri, 2023)
PT OSIN is a company that runs a business in the automotive manufacturing sector. The company applies aflow shop production model whose production pattern is line to line in series using the First Come FirstServe production scheduling method. The problem with the FCFS method which is considered to have notreached the optimal enough in meeting uncertain product demands, causing delays in the productionschedule, which has an impact on the flow or distribution of goods and can lead to increased production inactivities. The proposed improvement method is made to optimize production scheduling, focusing onminimizing the makespan values in the scheduling system's order. This study uses a heuristic approach tothe Campbell, Dudek, Smith (CDS) algorithm in overcoming scheduling problems. The CDS method is aproduction scheduling heuristic method developed from the Johnson algorithm in obtaining severalsequences of 6 types of work processes at the work center which aims to analyze the total time for eachprocessing process (makespan). Comparing the two methods using the FCFS method by sorting thescheduling according to the order of the initial order time produces a total value of 2,408.75 minutes, whileusing the CDS algorithm which uses 5 iterations produces a minor matter of 881.3 minutes. Comparing theresults obtained by applying the scheduling system with the CDS method can be used as a proposedimprovement in overcoming the delay in delivery and the production scheduling process.